Le français en contact avec l’anglais - Marádi, Krisztina (Verbum – Analecta Neolatina, 2001)
English and French have always been closely connected but, nowadays, their cultural and historical contacts have changed to such an extent that French can be considered as the most anglicised Romance language. The beginning of the domination of English dates from the 18th century, but the mass flow of English loan-words characterizes rather the 19th and 20th centuries and this tendency keeps accelerating day by day.